Green Procurement as a Tool in Maximizing Customer Satisfaction in a Manufacturing Organisation: A Case of BIDCO Kenya - Langat, Evans; Otieno, Benard (International Journal of Supply Chain Management, 2022)
Purpose: The purpose of this study was to do an assessment of how sustainable green procurement is a tool for customer satisfaction with reference to BIDCO Africa in Thika. This study was guided by the following research objectives: to establish the role of corporate social responsibility in customer satisfaction and to determine the role of reverse logistics in customer satisfaction. Methodology: The study adopted a descriptive research design. The target population in the study was 400 employees working with BIDCO. Sampling technique was used to ensure that each case in the population has an equal chance of being included in the sample. A questionnaire was used as a data collection instrument that aided to collect the relevant information needed for analysis. After collection of data it was analyzed using descriptive statistics methods such as mean, weighted averages and percentages. The analyzed data was presented by use of frequency tables, charts and graphs. Regression analysis was also applied where computer software was used also that is Statistical Package for Social Sciences (SPSS) for data analysis. Findings: The results indicated that there was positive relation between green procurement and customer satisfaction and the researcher recommended more application of the variables used in this study to increase on the customer satisfaction of manufacturing organization. Further studies recommended a comprehensive study to be done using both questionnaires, interviews and any other method of data collection to obtain in-depth information that the researcher missed in this study. System theory was tested by the researcher, This theory was used to describe an organization as a system that requires interrelation of all parts and change at one point may lead to multiple changes of other parts, (Maignan, 2012).organizations should operate as open systems where it should interact with the environment, even as many firms are painting their products green and they are not environmental friendly. Unique Contribution to Theory, Practice and Policy: The study recommends that with the global warming and environmental concerns from all sectors, there's is need for manufacturing organizations in Kenya to adopt green procurement practices in order to help in efforts of conserving the environment.